2010
DOI: 10.1089/neu.2009.1063
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Tensor Imaging at 3 Hours after Traumatic Spinal Cord Injury Predicts Long-Term Locomotor Recovery

Abstract: Accurate diagnosis of spinal cord injury (SCI) severity must be achieved before highly aggressive experimental therapies can be tested responsibly in the early phases after trauma. These studies demonstrate for the first time that axial diffusivity (ljj), derived from diffusion tensor imaging (DTI) within 3 h after SCI, accurately predicts long-term locomotor behavioral recovery in mice. Female C57BL=6 mice underwent sham laminectomy or graded contusive spinal cord injuries at the T9 vertebral level (5 groups,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
87
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(93 citation statements)
references
References 48 publications
(66 reference statements)
5
87
0
1
Order By: Relevance
“…Whereas changes in diffusivity related to Wallerian degeneration has been a focus of DTI studies after injury, GM diffusion changes suggest that the entire spinal cord is involved. 23,[43][44][45] A limited number of studies have reported diffusion characteristics from GM regions, and it is thought that some of these changes occur because of astrocytic activity in GM triggered by Wallerian degeneration in WM. 28,38,46 The similarity of changes in diffusion of both GM and WM is also consistent with a generalized change in water balance throughout the spinal cord.…”
Section: Figmentioning
confidence: 99%
“…Whereas changes in diffusivity related to Wallerian degeneration has been a focus of DTI studies after injury, GM diffusion changes suggest that the entire spinal cord is involved. 23,[43][44][45] A limited number of studies have reported diffusion characteristics from GM regions, and it is thought that some of these changes occur because of astrocytic activity in GM triggered by Wallerian degeneration in WM. 28,38,46 The similarity of changes in diffusion of both GM and WM is also consistent with a generalized change in water balance throughout the spinal cord.…”
Section: Figmentioning
confidence: 99%
“…Recent developments in MR pulse sequence design have greatly reduced these problems (Thurnher and Law 2009;Wilm, Gamper et al 2009;Wilm, Svensson et al 2007). Clinical findings correlate with DTI metrics of the injured spinal cord (Budzik, Balbi et al 2011;Chang, Jung et al 2010;Kim, Loy et al 2010;Qian, Chan et al 2011). Few studies have explored the relationship between structural integrity, evaluated using DTI, and physiological function of the human spinal cord Kerkovsky, Bednarik et al 2011;Qian, Chan et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In the experimental allergic encephalomyelitis model of multiple sclerosis, contrast changes have been observed in conventional anatomic images (Schellenberg et al, 2007), axial diffusivity has been correlated with axonal damage (Budde et al, 2008;Budde et al, 2007;Budde et al, 2009), and decreased quantitative T2 and magnetic transfer values have been shown (McCreary et al, 2009). Numerous studies have also assessed white matter integrity in mouse models of spinal cord injury, using diffusion tensor imaging Kim et al, 2010;Loy et al, 2007;Tu et al, 2010), T1-and T2-weighted imaging (Gonzalez-Lara et al, 2009;Levene et al, 2008;Nishi et al, 2007), and MRM (Bilgen, 2007). In mouse models of ALS, MRM has been used to show a decrease in total white matter volume of the spinal cord (Petrik et al, 2007) …”
Section: Introductionmentioning
confidence: 99%